Clinical, fiscal and environmental benefits of a specialist‐led virtual ureteric colic clinic: a prospective study. (2nd July 2019) - Connor, Martin J.; Miah, Saiful; Edison, Marie Alexandra; Brittain, James; Smith, Mitra Kondjin; Hanna, Milad; El‐Husseiny, Tamer; Dasgupta, Ranan
Abstract : Objectives: To evaluate the clinical, fiscal and environmental impact of a specialist‐led acute ureteric colic virtual clinic (VC) pathway. Patients and Methods: All patients with uncomplicated acute ureteric colic, referred to a single tertiary centre, were prospectively entered into the study over a 4‐year period (January 2015–December 2018). Inclusion criteria were: low‐dose non‐contrast computed tomography of kidneys, ureters and bladder; white blood cell count <16 × 109/L; pain controlled; normal renal function; and no clinical concern. Primary outcomes were: time (days) from referral to VC outcome; VC outcome (discharge, further VC, face‐to‐face [FTF] clinic, extracorporeal shockwave lithotripsy [ESWL], ureterorenoscopy [URS], percutaneous nephrolithotomy [PCNL]); and adverse events (sepsis or obstruction). Secondary outcomes were patient and stone demographics, cost and environmental analysis. The minimum follow‐up was 3 months. Results: A total of 1008 patients entered the study, of whom 91.5% ( n = 922) were of working age. The median (interquartile range) time from presentation to VC outcome was 2 (4) days. VC outcomes were as follows: 16.3% of patients ( n = 164) were discharged; 18.2% ( n = 183) were discharged after further VC; 17.2% ( n = 173) underwent an intervention; and 48.4% ( n = 488) were referred to an FTF clinic. Interventions comprised: PCNL 0.5% ( n = 5); ESWL 7.7% ( n = 78); and URS 8.9% ( n = 90). Stone demographics were as follows: 570 patients (56.5%) had lower, 157 (15.6%) had upper, 96 (9.5%) had mid‐ureteric and 163 (16.2%) had renal calculi, and in 22 patients (2.2%) the stones had recently passed. The mean (sd ) stone size was 3.5 (2.3) mm. Two adverse events (0.2%) were reported. Introducing a VC saved £145, 152 for Clinical Commissioning Groups, the equivalent NHS tariff payment of performing 106 URS procedures or 211 ureteric stent insertions. Overall, 15, 085 patient journey kilometres were avoided, equal to 0.70–2.93 metric tonnes of carbon dioxide equivalent production and the need to plant 14.7 trees to achieve carbon balance. Conclusion: A specialist‐led acute ureteric colic VC reduced time to treatment decision to a median of 2 days. This creates additional clinic capacity and reduces the fiscal burden of traditional clinics and their associated carbon footprint.